Twin crane scheduling with container reshuffling in container terminals - Lim, Ting Jie (Nanyang Technological University, 2020)
Port terminals are increasingly automating container operations to keep up with rising global trade volumes, including yard crane operations. Much of the space in terminals are taken up by yard block—temporary holding sites for containers handled by yard cranes. Containers in a yard block are stacked to save space, but this results in reshuffling when a container to be retrieved is blocked by containers stacked above it. Basic yard crane scheduling algorithms usually assume all containers to be retrieved are at the top of the stack. This project investigates the effect of reshuffling on the efficiency of twin-crane yard operations, where two cranes handle a yard block but are unable to pass each other. For this project, reshuffling works by shifting blocking containers to the nearest lowest-tier stack of the bay. A yard crane scheduling algorithm that uses non-zero-sum game theory is adopted to minimise the impact of reshuffling on yard crane productivity, measured by the time taken for a yard block to complete a set of yard crane jobs and the average waiting time of container trucks. Through simulation, the performance of the algorithm under various setting are evaluated. Desirable results were obtained in general, and workarounds suggested where results were less desirable.